Mordant inspired wet-spinning of graphene fibers for high performance flexible supercapacitors. Issue 12 (6th March 2019) - He, Nanfei; Shan, Weitao; Wang, Julia; Pan, Qin; Qu, Jiangang; Wang, Guofeng; Gao, Wei
Abstract : Al 3+ coagulated wet-spun graphene fibers show a large surface area and high electrical conductivity, resulting in large capacitance. Abstract : Recently, graphene fibers derived from wet-spinning of graphene oxide (GO) dispersions have emerged as viable electrodes for fiber-shaped supercapacitors (FSCs) and/or batteries, wherein large surface area, high electrical conductivity, and sufficient mechanical strength/toughness are desired. However, for most fiber electrodes reported so far, compromises have to be made between energy-storage capacity and mechanical/electrical performance, whereas a graphene fiber with high capacity and sufficient toughness for direct machine weaving or knitting is yet to be developed. Inspired by the alum mordant used for natural dyes in the traditional textile dyeing industry, our research group has synthesized wet-spun GO fibers and coagulated them with different multivalent cations ( e.g. Ca 2+, Fe 3+, and Al 3+ ), where dramatically different fiber morphologies and properties have been observed. The first principles density functional theory has been further employed to explain the observed disparities via cation–GO binding energy calculation. When assembled into solid-state FSCs, Al 3+ -based reduced GO (rGO) fibers offer excellent stability against bending, and a specific capacitance of 148.5 mF cm −2 at 40 mV s −1, 1.4, 4.8, and 6.8 times higher than that of the rGO fibers based on other three coagulation systems (Fe 3+, Ca 2+ and acetic acid), respectively. The volumetric energy density of the Al 3+ -based FSC is up to 13.26 mW h cm −3, while a high power density of 250.87 mW cm −3 is maintained.